Inovasi Pendekatan Holistik dalam Transformasi Pendidikan Dayah Masa Depan - Saifuddin, Saifuddin (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This article reviews the transformation of Dayah education with a focus on holistic approach innovation as a systematic solution to address the challenges of Islamic education in Aceh. This research is qualitative research which aims to deepen understanding of holistic approach innovation in the context of the future transformation of Dayah education. The analysis results show that a holistic approach with three main aspects (connectedness, openness, and balance) forms an integrated system, resulting in a comprehensive educational experience. This innovation makes Dayah education a forum that combines local wisdom with global demands, producing graduates who are strong in an era of change. Holistic innovation provides a responsive foundation for future needs, making a positive contribution to the development of students in all aspects. Overall, a holistic approach is a comprehensive solution to improve the quality of Dayah education in facing the dynamics of the times